Cloud based secured framework for implementation of online voting system - K S Gururaj; Dr K Thippeswamy (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Accessing and Utilization of data and information from remote location is one of the major requirements of present world. Due to the increase in the requirement of the data access from remote locations, challenges in the enhancement of technology based systems also have increased proportionately. Technology based solution for accessibility of remote data with available infrastructure is the need of the hour. Implementation of technology based solutions for the challenges may be expensive due to the current technical limitations. In this paper, we have attempted to design a secured cloud based framework for Online Voting System and analyzed its performance based on the three cryptographic algorithms namely Blowfish, AES and RSA.